2003
DOI: 10.1001/archpsyc.60.8.817
|View full text |Cite
|
Sign up to set email alerts
|

Depression With Atypical Features in the National Comorbidity Survey

Abstract: This analysis of a nationally representative US sample suggests that overeating and oversleeping can be used to identify an atypical depression subgroup that is distinct from other depressed patients in terms of demographics, psychiatric comorbidities, and abuse history. Findings also suggest that atypical depression is associated with increased distress, suicidal ideation, and disability compared with nonatypical depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
149
3
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(185 citation statements)
references
References 45 publications
23
149
3
8
Order By: Relevance
“…Subsequent studies of treatment-seeking patients also found patients with atypical depression have an earlier age of onset (Posternak and Zimmerman, 2002;Perugi et al, 1998;Benazzi, 1999) and a more chronic illness (McGinn et al, 1996;Posternak and Zimmerman, 2002) than other depressed patients. Corroboration by epidemiological studies (Angst et al, 2002;Matza et al, 2003;Kendler et al, 1996) suggests these findings are not artifacts of self-selection or referral bias. Despite occasional discrepancies (Benazzi, 1999;Asnis et al, 1995), the preponderance of evidence is that early onset and chronic illness characterize atypical depression relative to other depressed patients.…”
Section: Course Of Illnessmentioning
confidence: 88%
“…Subsequent studies of treatment-seeking patients also found patients with atypical depression have an earlier age of onset (Posternak and Zimmerman, 2002;Perugi et al, 1998;Benazzi, 1999) and a more chronic illness (McGinn et al, 1996;Posternak and Zimmerman, 2002) than other depressed patients. Corroboration by epidemiological studies (Angst et al, 2002;Matza et al, 2003;Kendler et al, 1996) suggests these findings are not artifacts of self-selection or referral bias. Despite occasional discrepancies (Benazzi, 1999;Asnis et al, 1995), the preponderance of evidence is that early onset and chronic illness characterize atypical depression relative to other depressed patients.…”
Section: Course Of Illnessmentioning
confidence: 88%
“…4 Others have found an association between history of physical or sexual abuse (SA) in childhood and MDD with reversed neurovegetative signs. 5,6 Physical or SA has also been linked to MDD with psychotic features (as opposed to MDD without psychotic features). 7 Nevertheless, it is not clear whether childhood trauma is linked more broadly and nonspecifically to depressive symptomatology, or if it is associated with more specific features of this heterogeneous disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Özellikle monoamin oksidaz (MAO) inhibitörü ilaçlara yanıt veren depresyon tipi olarak tanımlanmıştır. [2] Klein ve Davis depresyon tanısı almış bu hastalarda bir alt grup olarak histeroid disfori kavramını öne sürmüştür. Tanımlanan bu alt grup, genellikle kadın, atipik özellikli, histrionik görünümlü, kişisel reddedilmeye aşırı tahammülsüz, özellikle romantik ilişki kaybına duyarlılığı olan bir gruptu.…”
unclassified